Functionalized polar Octa(γ-chloropropyl) polyhedral oligomeric silsesquioxane assisted polyimide nanofiber composite membrane with excellent ionic conductivity and wetting mechanical strength towards enhanced lithium-ion battery. (26th May 2020) - Deng, Nanping; Wang, Lu; Liu, Yong; Zhong, Chongli; Kang, Weimin; Cheng, Bowen
Abstract: Based on the urgent demand of excellent wetting mechanical strength electrospun nanofiber separators and some doping compounds which are beneficial to enhance electrochemical performance for Li-ion cell, in this study, a natty nanofiber composite membrane based on heat-resistant polyimide (PI) matrix via introducing polar Octa (γ-chloropropyl) polyhedral oligomeric silsesquioxane (OCP-POSS) nanoparticles for the first time is resoundingly prepared by electrospinning technology. The hybrid PI/OCP-POSS separator (HOPS separator) with 3.5 wt% OCP-POSS nanoparticles presents significant improvement in wetting mechanical strength (11.8 MPa), eminent electrolyte retention rate (1025%) together with a tendency of gelation phase and still exerts laudable high thermal stability. Meanwhile, the battery with the HOPS separator exhibits preferable electrochemical stability window (5.2 V) and exceedingly excellent ionic conductivity (2.8 × 10 −3 S cm −1 ). The most extraordinary is that the capacity retention reaches up to 81.45% after 100 cycles at 0.2 C and 91.96% in C-rates test, while the pristine PI separator merely achieves to 56.03% and 75.90%, respectively. In addition, the modified separator possesses more stable cycling properties than PP separator (Celgard 2400) at 1 C and 2 C rate, respectively, which all fully signifies that the heat-resistant HOPS separator has great application prospects in high-performance and advanced-safety lithium-ion battery. Highlights: A novel heat-resistant PI/OCP-POSS separator was prepared by electrospinning. The additive amount of polar OCP-POSS effecting on PI membrane was investigated. The HOPS membrane had outstanding excellent ionic conductivity and wetting mechanical strength. The separator achieved higher capacity retention and better rate capability for lithium-ion battery.